High Performance Elliptic Curve GF(2m) Crypto-processor - Al-Somani, Turki Faisal (2006)
This study presents a high performance elliptic curve cryptoprocessor architecture over GF(2m). The proposed architecture exploits parallelism at the projective coordinate level to perform parallel field multiplications. Comparisons between the Projective, Jacobian and Lopez-Dahab coordinate systems using sequential and parallel designs are presented. Results show that parallel designs gives better area-time complexity (AT2) than sequential designs by 44-252% which leads to a wide range of design tradeoffs. The results also show that the Projective coordinate system gives the best AT2 in parallel designs with the least number of multiplications levels when using 4 multipliers.